ANALISA STRATEGI BAURAN PEMASARAN JASA DAN CITRA DALAM MENINGKATKAN KEPUASAN DAN LOYALITAS KONSUMEN (STUDI PADA KBIH MIFTAHUL ULUM LUMAJANG) - M. HASIB ABDULLAH (Jurnal Ekonomi Syariah Darussalam, 2024)
The focus of this research is: 1) Marketing mix strategy carried out by KBIH Miftahul Ulum Lumajang, 2) KBIH Miftahul Ulum Lumajang in forming the company image, 3) KBIH Miftahul Ulum Lumajang in increasing consumer satisfaction, 4) KBIH Miftahul Ulum Lumajang increases consumer loyalty, 5) Obstacles in implementing the marketing mix strategy in KBIH Miftahul Ulum Lumajang, 6) Solutions to overcome problems in the marketing mix strategy. The research method used uses a qualitative approach and descriptive research type. The research results show that service quality and product quality are seen as components that need to be realized by companies, because they have the influence of bringing in new consumers and can reduce the possibility of old customers moving to other companies. Customer loyalty has motivational and behavioral consequences. When we give consumers what they want, consumers will get satisfaction, which can give rise to consumer loyalty.